Salinity induced oxidative stress enhanced biofuel production potential of microalgae Scenedesmus sp. CCNM 1077. (August 2015) - Pancha, Imran; Chokshi, Kaumeel; Maurya, Rahulkumar; Trivedi, Khanjan; Patidar, Shailesh Kumar; Ghosh, Arup; Mishra, Sandhya
Graphical abstract: Highlights: Salinity stress affects physiological and biochemical composition of microalgae. 33.13% lipid and 35.91% carbohydrate accumulated under 400 mM NaCl stress. Oxidative stress is important for neutral lipid accumulation. Two stage salinity stress is best approach for biomass and lipid production. Scenedesmus sp. is a potential feedstock for biofuels production. Abstract: Microalgal biomass is considered as potential feedstock for biofuel production. Enhancement of biomass, lipid and carbohydrate contents in microalgae is important for the commercialization of microalgal biofuels. In the present study, salinity stress induced physiological and biochemical changes in microalgae Scenedesmus sp. CCNM 1077 were studied. During single stage cultivation, 33.13% lipid and 35.91% carbohydrate content was found in 400 mM NaCl grown culture. During two stage cultivation, salinity stress of 400 mM for 3 days resulted in 24.77% lipid (containing 74.87% neutral lipid) along with higher biomass compared to single stage, making it an efficient strategy to enhance biofuel production potential of Scenedesmu s sp. CCNM 1077. Apart from biochemical content, stress biomarkers like hydrogen peroxide, lipid peroxidation, ascorbate peroxidase, proline and mineral contents were also studied to understand the role of reactive oxygen species (ROS) mediated lipid accumulation in microalgae Scenedesmus sp. CCNM 1077.